The Evaluation and Improvement of Children Friendliness in Urban Village Space in Foshan - Yongming, YANG; Raja Nur Syaheeza, Raja Mohd Yazit; Julaihi, Wahid (Journal of Information Systems Engineering and Management, 2025)
his study aims to evaluate child friendliness in urban village spaces and propose strategies for improvement. There are approximately 116 urban villages in Foshan, where urban villages serve as an important spatial carrier for children's growth and life. The friendliness of the space environment for children has significant implications for their growth. This study starts from the perspective of child-friendliness and, through a literature review, points out that the human settlement discipline in various countries has increasingly attached importance to the child population, and the research trend has shown a vigorous interdisciplinary development. Researchers have systematically studied the planning and environmental design of children's spaces, but research on the child-friendly environment of urban villages is still insufficient. In recent years, the research scope and methods have been updated to provide a foundation for child-friendly residential environment research. This study conducted a spatial environment survey of 18 urban villages from March to May 2023, including alleys, outdoor spaces, and children's activities, using field observation to record children's behaviors and spatial features. Five key villages were selected for a survey of children's activity characteristics, and data were collected through field observation, questionnaires, and interviews. Based on the indicators proposed by Meng Xue (2020), a five-point scale was used to collect parents' opinions and analyze the child-friendliness. The outdoor space environmental elements were analyzed using spatial analysis tools, and the interview and questionnaire data were sorted and charted using Excel 2019. Through on-site investigation and analysis, key findings indicate that safety hazards, limited facilities, and inadequate green spaces constrain the child-friendliness of urban villages. The study, based on the investigation findings, proposed the following improvement suggestions based on the investigation results: (1) Enhancing the safety and suitability of road space: establishing safe road space, setting up suitable pedestrian systems and continuous school pathways, partitioning restrictions on vehicle access, conducting safety knowledge education, and utilizing electronic monitoring to ensure safety. (2) Increasing green space area and creating high-quality playgrounds: concentrating on building parking buildings to release space, differentiating park green space configuration to allocate game facilities, and utilizing scattered plots to build point-shaped small parks. In the end, the article combined the child-friendly space construction guidelines to propose the following design strategies to enhance the child-friendliness of the urban village space environment: (1) Solving vehicle parking problems; (2) transforming road cross-section; (3) planning children's commuting routes; (4) child-friendly transformation of roads; (5) adding children's service facilities; (6) child-friendly transformation of green space; (7) utilizing marginal spaces. This research applies child-friendly design principles to urban villages, a setting that has been previously underexplored. The findings align with biophilia theory, emphasizing children's need for natural and engaging spaces. Future research should incorporate children's perspectives and expand other urban settings.